Increased malaria parasitaemia among adults living with HIV who have discontinued cotrimoxazole prophylaxis in Kitgum district, Uganda - Orishaba, Philip; Kalyango, Joan N.; Byakika-Kibwika, Pauline; Arinaitwe, Emmanuel; Wandera, Bonnie; Katairo, Thomas; Muzeyi, Wani; Tendo Nansikombi, Hildah; Nakato, Alice; Mutabazi, Tobius; Kamya, Moses R.; Dorsey, Grant; et al. (PLoS ONE, 2020)
Although WHO recommends cotrimoxazole (CTX) discontinuation among HIV patients who have undergone immune recovery and are living in areas of low prevalence of malaria, some countries including Uganda recommend CTX discontinuation despite having a high malaria burden. We estimated the prevalence and factors associated with malaria parasitaemia among adults living with HIV attending hospital outpatient clinic before and after discontinuation of CTX prophylaxis.
Keywords: Malaria parasitaemia; Adults; HIV; Cotrimoxazole prophylaxis; Uganda